Covid-19 and caste inequalities in India: the critical role of social identity in pandemic-induced job losses - Deshpande, Ashwini; Ramachandran, Rajesh (Applied economic perspectives and policy, 2023)
Using panel data for the period between April 2019 and September 2021, this paper investigates how the Covid-19 pandemic-induced lockdowns imposed differential labor market shocks on different social identity groups. We find that while all caste groups lost jobs in the first 2 months of the lockdown, the job losses for lowest-ranked caste are greater by factor of more than two. The data shows that caste gaps in employment outcomes remain sizeable, even when we compare groups within the same industry, occupations, or those who have completed secondary schooling. These findings suggest that caste is not merely a proxy for class, and identity-based policies might be essential to overcoming these disparities.